Ni / Cu-TiO2 nanocatalyst and its preparation method and application

By dispersing Ni nanoparticles on Cu-TiO2 nanosheets, regulating Cu doping and defective structure, the problems of low activity and easy agglomeration of non-precious metal catalysts are solved, and efficient and stable hydrogen production by hydrazine hydrate is achieved, providing high selectivity and durable Ni/Cu-TiO2 nanocatalyst.

CN118767919BActive Publication Date: 2024-12-27JIANGXI NORMAL UNIV
View PDF 16 Cites 0 Cited by

Patent Information

Application Number
CN202411252675.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-09
Publication Date
2024-12-27
Estimated Expiration
2044-09-09

AI Technical Summary

Technical Problem

Existing non-precious metal catalysts have low catalytic activity and are prone to agglomeration in the decomposition reaction of hydrazine hydrate, making it difficult to achieve efficient and stable hydrogen production.

Method used

Using Ni/Cu-TiO2 nanocatalyst, Cu-TiO2 nanosheets were synthesized by hydrothermal method as support, Ni nanoparticles were dispersed, Cu doping amount and defect structure were regulated, the electronic structure and active sites of Ni were optimized, and catalytic activity was improved.

Benefits of technology

High selectivity and stable hydrogen production of hydrazine hydrate is achieved, the catalyst exhibits 100% H2 selectivity and significant durability, the catalytic reaction rate is improved, the conversion frequency is as high as 524 h-1, and the cost is low.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118767919B_ABST
    Figure CN118767919B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of catalysts, and specifically relates to a Ni / Cu‑TiO2 nanocatalyst and a preparation method and application thereof. The Ni / Cu‑TiO2 nanocatalyst comprises Cu‑TiO2 nanosheets and Ni nanoparticles dispersed on the Cu‑TiO2 nanosheets; the average particle size of the Ni nanoparticles is 1.2 nm‑3.0 nm, and the content of Ni is 22.6wt%‑53.9 wt%. The present invention synthesizes Cu‑TiO2 nanosheets by a hydrothermal method using titanyl sulfate as a titanium source and cupric chloride as a dopant, and uses the nanosheets as a carrier to prepare a Cu‑TiO2-loaded Ni nanocatalyst by a simple, green and low-cost wet chemical method. The catalyst exhibits excellent catalytic performance, 100% H2 selectivity and significant durability, and the TOF value of catalyzing the decomposition of hydrazine hydrate to produce hydrogen at 343 K is 302 h ‑1 .
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalysts, and specifically relates to a Ni / Cu-TiO2 nanocatalyst and a preparation method and application thereof. Background Art

[0002] As a green and sustainable energy carrier, hydrogen (H2) has attracted much attention due to its huge energy density and environmental friendliness. However, the safe and efficient storage of hydrogen remains a key challenge. Nowadays, chemical hydrogen storage has been recognized as an efficient and convenient method. Hydrazine hydrate (N2H4·H2O) has become a highly regarded chemical hydrogen storage material due to its high capacity (8.0 wt%) and safe storage and transportation. Under suitable catalysts and reaction conditions, N2H4 can be completely decomposed into H2 and N2 (reaction (1)). However, if the catalyst or reaction conditions are not suitable, the decomposition of N2H4 can also be through an incomplete decomposition route (reaction (2)), that is, decomposition into NH3 and N2, which reduces the hydrogen production efficiency, and the generated NH3 can poison the catalyst. Therefore, the development of highly selective and highly stable catalytic materials is of great significance to achieve complete hydrogen production from N2H4.

[0003] N2H4(1) → N2(g) + 2H2(g) (1)

[0004] 3N2H4(1) → 4NH3(g) + N2(g)(2)

[0005] Currently, most of the efficient catalysts for hydrazine hydrate decomposition to produce hydrogen contain precious metals. Non-precious metal catalysts, especially nickel catalysts, have been shown to have good activity and selectivity in hydrazine hydrate hydrolysis, but their catalytic activity is still unsatisfactory compared with precious metal-based catalysts, and they are prone to agglomeration. Therefore, there is an urgent need to develop cost-effective non-precious metal catalysts for the rapid catalytic decomposition of hydrazine hydrate to produce hydrogen. Summary of the invention

[0006] The purpose of the present invention is to solve the problems of low catalytic activity and easy agglomeration of non-precious metal catalysts in the prior art, and to provide a Ni / Cu-TiO2 nanocatalyst and a preparation method and application thereof, which specifically adopts the following technical solutions:

[0007] In a first aspect of the present invention, a Ni / Cu-TiO2 nanocatalyst is provided, which comprises Cu-TiO2 nanosheets and Ni nanoparticles dispersed on the Cu-TiO2 nanosheets; the average particle size of the Ni nanoparticles is 1.2 nm-3.0 nm, and the Ni content is 22.6wt%-53.9 wt%.

[0008] The Ni / Cu-TiO2 nanocatalyst of the present invention has excellent activity due to the strong metal-carrier interaction, ultrafine Ni metal nanoparticles and the electronic regulation effect of the defect-rich and abundant Cu-O-Ti interface on Ni. The catalyst has the characteristics of small particle size, multiple catalytic active sites, and high catalytic activity and stability, and is a catalyst with great development prospects.

[0009] As a further preferred embodiment, the size of the Cu-TiO2 nanosheets in the above-mentioned Ni / Cu-TiO2 nanocatalyst is 5 nm-15 nm; the content of Cu in the above-mentioned Ni / Cu-TiO2 nanocatalyst is 2.6 wt%-5.8 wt%.

[0010] The second aspect of the present invention provides a method for preparing the above-mentioned Ni / Cu-TiO2 nanocatalyst, comprising the following steps:

[0011] Disperse Cu-TiO2 powder in water, add nickel source precursor, and ultrasonicate to obtain a suspension;

[0012] A reducing agent is added to the suspension to carry out a reduction reaction until no bubbles are generated, thereby obtaining a Ni / Cu-TiO2 nanocatalyst.

[0013] The invention uses a hydrothermal method to synthesize Cu-TiO2 nanosheets using titanyl sulfate as a titanium source and cupric chloride as a dopant, and uses the nanosheets as a carrier. In the hydrothermal process, some Ti atoms of the Cu-TiO2 nanosheet carrier are replaced by Cu atoms, resulting in self-doping disorder of TiO2, forming oxygen vacancies and Cu-O-Ti interfaces, which is conducive to optimizing the electronic structure of active metal Ni, exposing more active sites, and improving the electronic structure of active metal Ni nanoparticles, thereby improving the catalyst activity. In addition, the Cu-TiO2 with abundant defects makes it easier for reactants to be adsorbed and activated, which can further improve the catalyst activity.

[0014] As a further preferred embodiment, the Cu-TiO2 powder is obtained by the following steps:

[0015] Titanyl sulfate, anhydrous ethanol, water, glycerol and cupric chloride are mixed and stirred to obtain a suspension;

[0016] The suspension was placed in a temperature-controlled oven of an autoclave and heated to 180°C-220°C. After heating, it was cooled to room temperature, and then washed with ethanol and water in sequence and dried to obtain Cu-TiO2 powder.

[0017] During the hydrothermal process of the Cu-TiO2 powder, some Ti atoms are replaced by Cu atoms, resulting in disordered self-doping of TiO2, forming oxygen vacancies and Cu-O-Ti interfaces, which are conducive to the adsorption of metal precursors to obtain highly dispersed and small-sized metal nanoparticles, exposing more active sites, and also conducive to optimizing the electronic structure of active metal Ni nanoparticles, making their surface electron-rich, thereby significantly improving the catalyst activity. In addition, Cu-TiO2 with abundant defects makes reactants easier to adsorb and activate, which can further improve the catalyst activity.

[0018] As a further preferred embodiment, the usage ratio of the above-mentioned titanyl sulfate, anhydrous ethanol, water, glycerol and cupric chloride is 1.0 g-5.0 g: 10 mL-50 mL: 5 mL-10 mL: 1 mL-5 mL: 0.05 g-0.2 g.

[0019] The amount of copper chloride used in the above preparation process will affect the catalytic performance of the finally prepared Ni / Cu-TiO2 nanocatalyst. The defect content of the catalyst can be regulated by adjusting the amount of copper chloride used when synthesizing the Cu-TiO2 carrier. When Cu is doped into TiO2, its internal structure will be disordered, thereby generating a large number of oxygen defects. Cu-TiO2 with rich oxygen defects is not only conducive to obtaining highly dispersed small-sized metal nanoparticles, but also can regulate the electronic structure of the active metal so that its surface is in an electron-rich state. When the amount of copper chloride used is 0.15 g, the Ni / Cu-TiO2 nanocatalyst exhibits the best performance for the decomposition of hydrazine hydrate to produce hydrogen.

[0020] As a further preferred embodiment, the heating time is 6 h-12 h.

[0021] As a further preferred embodiment, the mass ratio of the Cu-TiO2 powder and the nickel source precursor is 48.6-72.6:10-40.

[0022] As a further preferred embodiment, the nickel source precursor includes at least one of nickel chloride, nickel nitrate or nickel sulfate; and the reducing agent includes sodium borohydride.

[0023] The third aspect of the present invention also provides the use of the above-mentioned Ni / Cu-TiO2 nanocatalyst in catalyzing the decomposition of hydrazine hydrate to produce hydrogen. The temperature at which the Ni / Cu-TiO2 nanocatalyst catalyzes the decomposition of hydrazine hydrate to produce hydrogen is 323 K-353 K. The Ni / Cu-TiO2 nanocatalyst catalyzes the production of hydrogen from hydrazine hydrate and shows 100% H2 selectivity. The catalytic reaction rate and the reaction activity are significantly improved with the increase of temperature. At 353 K, the prepared Ni / Cu-TiO2 nanocatalyst catalyzes the complete decomposition and dehydrogenation of hydrazine hydrate in only 2.3 min, and its conversion frequency (TOF) value is as high as 524 h -1 .

[0024] The beneficial effects of the present invention are:

[0025] (1) The present invention synthesizes Cu-TiO2 nanosheets by a hydrothermal method using titanyl sulfate as a titanium source and cupric chloride as a dopant, and uses the nanosheets as a carrier. Ultrafine Ni nanoparticles with an average particle size of about 1.2 nm to 3.0 nm are highly dispersed on the Cu-TiO2 nanosheets by a simple, green and low-cost wet chemical method to prepare Cu-TiO2-supported Ni nanocatalysts (Ni / Cu-TiO2). This method can regulate the defect content of the carrier Cu-TiO2 nanosheets and the Cu-O-Ti interface structure by regulating the amount of cupric chloride used in the synthesis process of the Cu-TiO2 nanosheets, thereby regulating the interaction between the non-precious metal Ni and the Cu-TiO2 nanosheets. Through XRD, Raman, EPR, FTIR, TEM and XPS characterization analysis, it can be seen that during the hydrothermal process of the carrier Cu-TiO2 nanosheets, some Ti atoms are replaced by Cu atoms, resulting in disordered self-doping of TiO2, forming oxygen vacancies and Cu-O-Ti interfaces, which is conducive to the adsorption of metal precursors to obtain highly dispersed and small-sized metal nanoparticles, exposing more active sites, and also conducive to optimizing the electronic structure of active metal Ni nanoparticles, making their surface electron-rich, thereby significantly improving the catalyst activity. In addition, Cu-TiO2 with abundant defects makes reactants easier to adsorb and activate, which can further improve the catalyst activity.

[0026] (2) The Ni / Cu-TiO2 catalyst prepared by the present invention exhibits excellent catalytic performance, 100% H2 selectivity and remarkable durability. The TOF value of the Ni / Cu-TiO2 for catalytic decomposition of hydrazine hydrate to produce hydrogen at 343 K is 302 h -1 .

[0027] (3) The catalyst provided by the present invention has the advantages of high efficiency, stability and low cost of preparation, and the catalyst accelerates the practical application of hydrazine hydrate as an efficient hydrogen supplier in fuel cells. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 Shown are X-ray diffraction patterns of the Ni / Cu-TiO2 nanocatalysts prepared in Examples 1 to 4 of the present invention and the Ni / TiO2 nanocatalyst prepared in Comparative Example 1;

[0029] Figure 2 Shown are Raman spectra of the Ni / Cu-TiO2 nanocatalysts prepared in Examples 1 to 4 of the present invention and the Ni / TiO2 nanocatalyst prepared in Comparative Example 1;

[0030] Figure 3 Shown are Fourier transform infrared spectra of the Ni / Cu-TiO2 nanocatalysts prepared in Examples 1 to 4 of the present invention and the Ni / TiO2 nanocatalyst prepared in Comparative Example 1;

[0031] Figure 4 Shown are electron paramagnetic resonance spectra of the Ni / Cu-TiO2 nanocatalysts prepared in Examples 1 to 4 of the present invention and the Ni / TiO2 nanocatalyst prepared in Comparative Example 1;

[0032] Figure 5 Shown are X-ray photoelectron spectra of the Ni / Cu-TiO2 nanocatalyst prepared in Example 1 of the present invention and the Ni / TiO2 nanocatalyst prepared in Comparative Example 1;

[0033] Figure 6 Shown are transmission electron microscope images of the Cu-TiO2 carrier prepared in Example 1 of the present invention (shown in a), transmission electron microscope images of the Ni / Cu-TiO2 nanocatalyst (shown in b and c), and a particle size statistics of Ni nanoparticles (shown in d);

[0034] Figure 7 Shown are the transmission electron microscope images (shown in a) of the Ni / TiO2 nanocatalyst prepared in Comparative Example 1 of the present invention and the particle size statistics of the Ni nanoparticles (shown in b);

[0035] Figure 8 Shown are the transmission electron microscope images (shown in a) of the Ni nanocatalyst prepared in Comparative Example 3 of the present invention and the particle size statistics of the Ni nanoparticles (shown in b);

[0036] Fig. 9 Shown is a test graph of hydrogen production performance of Ni / Cu-TiO2 nanocatalysts prepared in Examples 1 to 4 of the present invention and Ni / TiO2 nanocatalysts prepared in Comparative Example 1 by catalyzing the decomposition of hydrazine hydrate at 343 K;

[0037] Fig.10Shown is a performance graph of the Ni / Cu-TiO2 nanocatalyst prepared in Example 1 of the present invention and the Ni / TiO2, NiCu / TiO2 and Ni nanocatalysts prepared in Comparative Examples 1 to 3 catalyzing the decomposition of hydrazine hydrate to produce hydrogen at 343 K;

[0038] Fig.11 The figure shows the performance of the Ni / Cu-TiO2 nanocatalyst prepared in Example 1 of the present invention for catalyzing the decomposition of hydrazine hydrate to produce hydrogen at different temperatures;

[0039] Fig.12 The graph shows the cyclic performance of the Ni / Cu-TiO2 nanocatalyst prepared in Example 1 of the present invention in catalyzing the decomposition of hydrazine hydrate to produce hydrogen at 343 K. DETAILED DESCRIPTION

[0040] The following will be combined with the embodiments and drawings to clearly and completely describe the concept, specific structure and technical effects of the present invention, so as to fully understand the purpose, scheme and effect of the present invention. It should be noted that the embodiments and features in the embodiments of this application can be combined with each other without conflict.

[0041] Example 1

[0042] A method for preparing a Ni / Cu-TiO2 nanocatalyst comprises the following steps:

[0043] (1) Preparation of Cu-TiO2

[0044] 1.0 g of titanyl sulfate was added to a mixture containing 10 mL of anhydrous ethanol and 6 mL of deionized water. 1.5 mL of glycerol was slowly added dropwise under vigorous stirring, followed by rapid addition of 0.15 g of copper chloride and stirring for 1 h to form a suspension. The suspension was then transferred into a 100 mL autoclave and heated at 200 °C in a temperature-controlled oven for 8 h. After cooling naturally to room temperature, the product was washed alternately with ethanol and water, and then dried in a vacuum drying oven at 40 °C overnight to obtain a white Cu-TiO2 powder with a Cu content of 5.2 wt%;

[0045] (2) Preparation of Ni / Cu-TiO2 nanocatalyst

[0046] 30 mg of Cu-TiO2 white powder prepared in step 1 was dispersed in 5 mL of deionized water, 48.4 mg of nickel chloride was added, and ultrasonic treatment was performed at room temperature for 30 min. 30 mg of sodium borohydride was added for reduction until no bubbles were generated to obtain a Ni / Cu-TiO2 nanocatalyst with Ni and Cu contents of 28.1 wt% and 5.2 wt%, respectively.

[0047] Example 2

[0048] A method for preparing a Ni / Cu-TiO2 nanocatalyst, wherein the preparation method is similar to the method in Example 1, except that the amount of cupric chloride in step (1) of Example 1 is changed from 0.15 g to 0.05 g. The other steps are exactly the same, and a Ni / Cu-TiO2 nanocatalyst having Ni and Cu contents of 28.1 wt% and 2.6 wt%, respectively, is obtained.

[0049] Example 3

[0050] A method for preparing a Ni / Cu-TiO2 nanocatalyst, wherein the preparation method is similar to the method in Example 1, except that the amount of cupric chloride in step (1) of Example 1 is changed from 0.15 g to 0.10 g. The other steps are exactly the same, and a Ni / Cu-TiO2 nanocatalyst having Ni and Cu contents of 28.1 wt% and 4.7 wt%, respectively, is obtained.

[0051] Example 4

[0052] A method for preparing a Ni / Cu-TiO2 nanocatalyst, wherein the preparation method is similar to the method in Example 1, except that the amount of cupric chloride in step (1) of Example 1 is changed from 0.15 g to 0.2 g. The other steps are exactly the same, and a Ni / Cu-TiO2 nanocatalyst having Ni and Cu contents of 28.1 wt% and 5.8 wt%, respectively, is obtained.

[0053] Example 5

[0054] A method for preparing a Ni / Cu-TiO2 nanocatalyst, wherein the preparation method is similar to the method in Example 1, except that the nickel chloride in step (2) of Example 1 is replaced by nickel nitrate. The other steps are exactly the same, and a Ni / Cu-TiO2 nanocatalyst having Ni and Cu contents of 28.1 wt% and 5.2 wt%, respectively, is obtained.

[0055] Example 6

[0056] A method for preparing a Ni / Cu-TiO2 nanocatalyst, wherein the preparation method is similar to the method in Example 1, except that the nickel chloride in step (2) of Example 1 is replaced by nickel sulfate. The other steps are exactly the same, and a Ni / Cu-TiO2 nanocatalyst having Ni and Cu contents of 28.1 wt% and 5.2 wt%, respectively, is obtained.

[0057] Comparative Example 1

[0058] A method for preparing a Ni / TiO2 nanocatalyst, wherein the preparation method is similar to the method in Example 1, except that the amount of cupric chloride in step (1) of Example 1 is changed from 0.15 g to 0, and the other steps are exactly the same, thereby obtaining a Ni / TiO2 nanocatalyst with a Ni content of 28.1 wt%.

[0059] Comparative Example 2

[0060] A method for preparing a NiCu / TiO2 nanocatalyst, the preparation method is similar to the method in Example 1, except that the amount of cupric chloride in step (1) of Example 1 is changed from 0.15 g to 0; after adding 48.4 mg of nickel chloride in step (2) of Example 1, 5.8 mg of cupric chloride is also added, and the other steps are exactly the same, to obtain a NiCu / TiO2 nanocatalyst with Ni and Cu contents of 28.1 wt% and 5.2 wt%, respectively.

[0061] Comparative Example 3

[0062] A method for preparing a Ni nanocatalyst, wherein the preparation method is similar to the method of step (2) in Example 1, the only difference being that no Cu-TiO2 white powder is added in step (2), and the other steps are exactly the same as step (2) in Example (1), to obtain a Ni nanocatalyst.

[0063] The relevant characterization data of some materials prepared in the above examples are as follows:

[0064] Figure 1 The X-ray diffraction patterns of the Ni / Cu-TiO2 nanocatalysts prepared in Examples 1 to 4 of the present invention and the Ni / TiO2 nanocatalyst prepared in Comparative Example 1 are shown; and Figure 1 It can be seen that compared with Comparative Example 1, the 101 peak of TiO2 in the Ni / Cu-TiO2 prepared in Examples 1 to 4 showed a positive shift, which can be attributed to the fact that the incorporation of Cu into TiO2 destroys the crystal structure, and some Ti-O-Ti bonds break and recombine to form Cu-O-Ti bonds, confirming the existence of the Cu-O-Ti interface.

[0065] Figure 2 The Raman spectra of the Ni / Cu-TiO2 nanocatalysts prepared in Examples 1 to 4 of the present invention and the Ni / TiO2 nanocatalyst prepared in Comparative Example 1 are shown; and Figure 2It can be seen that compared with the Ni / TiO2 of Comparative Example 1, the Eg (1) peak in the Ni / Cu-TiO2 prepared in Examples 1 to 4 is slightly shifted to a higher wave number, which may be attributed to the doping of Cu into the TiO2 lattice, resulting in lattice disorder and the generation of oxygen vacancies required to maintain charge neutrality. In addition, with the increase in the amount of Cu doping, the degree of deviation gradually increases, and the symmetric stretching vibration of the Ti-O-Ti bond weakens, indicating that the Ti-O-Ti bond is destroyed and reorganized into a Cu-O-Ti bond, transitioning from the Ti-O-Ti interface to the Cu-O-Ti interface. In addition, the blue shift of Ni / Cu-TiO2 also confirms the strong interaction between Cu and TiO2.

[0066] Figure 3 The Fourier transform infrared spectra of the Ni / Cu-TiO2 nanocatalysts prepared in Examples 1 to 4 of the present invention and the Ni / TiO2 nanocatalyst prepared in Comparative Example 1 are shown; and Figure 3 It can be seen that 3478 and 1668 cm -1 The peak at 400–700 cm -1 The peak at is attributed to the Ti-O-Ti bridge tensile mode. In addition, it can be found that the Ti-O-Ti peak of Ni / Cu-TiO2 prepared in Examples 1 to 4 is wider than that of Ni / TiO2 prepared in Comparative Example 1 because the doping of Cu causes the self-doping disorder of TiO2, which weakens the tensile strength of Ti-O-Ti. This also proves again that when Cu is doped into TiO2, the Ti-O-Ti interface transforms into the Cu-O-Ti interface, which is consistent with the results of X-ray diffraction and Raman analysis.

[0067] Figure 4 The electron paramagnetic resonance spectra of the Ni / Cu-TiO2 nanocatalysts prepared in Examples 1 to 4 of the present invention and the Ni / TiO2 nanocatalyst prepared in Comparative Example 1 are shown; and Figure 4 It can be seen that there is a peak at a g value of 2.003, which is a characteristic peak of oxygen defects, and it can be found that the signal intensity of Ni / Cu-TiO2 prepared in Examples 1 to 4 is significantly stronger than that of Ni / TiO2 prepared in Comparative Example 1. This is because when Cu is doped into TiO2, its internal structure becomes disordered, thereby generating a large number of oxygen defects. Cu-TiO2 with rich oxygen defects is not only conducive to obtaining highly dispersed small-sized metal particles, but also can adjust the electronic structure of the active metal so that its surface is in an electron-rich state.

[0068] Figure 5 The X-ray photoelectron spectra of the Ni / Cu-TiO2 nanocatalyst prepared in Example 1 of the present invention and the Ni / TiO2 nanocatalyst prepared in Comparative Example 1 are shown; and Figure 5It can be seen that the high-resolution Ti 2pXPS spectrum of Ni / TiO2 prepared in Comparative Example 1 is convoluted into two Ti 4+ peaks (459.1 and 465.4 eV, Figure 5 a in the figure). The high-resolution Ti 2p XPS spectrum of Ni / Cu-TiO2 prepared in Example 1 is decomposed into four peaks ( Figure 5 (a) The two peaks at 458.8 and 464.9 eV are attributed to Ti 4+ 2p 3 / 2 and Ti 4+ 2p 1 / 2 , and the other two peaks at 457.2 and 462.8 eV were assigned to Ti 3+ 2p 3 / 2 or Ti 3+ 2p 1 / 2 , which confirms that Ti 3+ The species is formed after the introduction of Cu. In addition, the Ti of Ni / Cu-TiO2 prepared in Example 1 4+ 2p 3 / 2 and Ti 4+ 2p 1 / 2 The binding energy of Ni / Cu-TiO2 shows a positive shift, which may be attributed to the strong electronic effect and intermetallic interaction between TiO2 and Cu in Ni / Cu-TiO2. The O1s XPS spectrum of Ni / Cu-TiO2 prepared in Example 1 reveals the presence of O-Ti groups (531.3 eV), OH-Ti groups (533.2 eV) ( Figure 5 b). Cu 2pXPS spectrum of Ni / Cu-TiO2 prepared in Example 1 ( Figure 5 c) shows that 949.6 eV and 929.7 eV are respectively attributed to Cu 2+ Cu 2p 1 / 2 and Cu 2p 3 / 2 The other peaks at 951.9 eV and 931.9 eV may be related to Cu + The Ni 2p of Ni / Cu-TiO2 prepared in Example 1 is related to the species, indicating that the Cu atom is not 0-valent and is not simply physically adsorbed on the TiO2 surface. 3 / 2 spectrum( Figure 5 (d) shows a peak at about 852.9 eV attributed to metallic Ni 0 (2p 3 / 2 ) peak, while the Ni 2p peak at 856.4 eV 3 / 2 The peak belongs to Ni 2+ This may be due to the partial oxidation of the catalyst during sample preparation. Its satellite peak is approximately 3 / 2In addition, compared with the binding energy of Ni / TiO2 prepared in Comparative Example 1 (853.4 eV), the Ni 2p 3 / 2 The peak moves to a lower binding energy. Therefore, compared with TiO2, the Cu-O-Ti interface of Cu-TiO2 can provide more electrons to Ni. The above XPS analysis results show that the Cu-O-Ti interface formed by doping Cu into the carrier TiO2 can increase the electron density on the surface of the active metal Ni, which will help promote the breaking of the NH bond and thus improve the catalytic activity.

[0069] Figure 6 Shown are transmission electron micrographs of the Cu-TiO2 carrier prepared in Example 1 of the present invention (shown in a), transmission electron micrographs of the Ni / Cu-TiO2 nanocatalyst (shown in b and c), and a particle size statistical diagram of Ni nanoparticles (shown in d); and Figure 6 It can be seen that Ni nanoparticles with an average size of 1.2 nm are uniformly dispersed on the Cu-TiO2 nanosheets.

[0070] Figure 7 The figure shows the transmission electron microscope image (shown in a) of the Ni / TiO2 nanocatalyst prepared in Comparative Example 1 of the present invention and the particle size statistics of the Ni nanoparticles (shown in b); and Figure 7 It can be seen that the Ni nanoparticles supported by TiO2 without Cu doping are larger in size (3.2 nm).

[0071] Figure 8 Shown are the transmission electron microscope images (shown in a) of the Ni nanocatalyst prepared in Comparative Example 3 of the present invention and the particle size statistics of the Ni nanoparticles (shown in b); and Figure 8 It can be seen that the Ni nanoparticles without carrier immobilization are severely agglomerated and have a large size (11.6 nm).

[0072] Example 7

[0073] The Ni / Cu-TiO2 nanocatalyst prepared in Examples 1 to 4 of the present invention is used to catalyze the decomposition of hydrazine hydrate to produce hydrogen, and the specific process is as follows:

[0074] The catalyst was placed in a 50 mL flask containing 5 mL of deionized water, and then 12.5 mmol of NaOH was added. The amount of the catalyst was the amount of the catalyst prepared in each example. 100 μL (2 mmol) of hydrazine hydrate was added at 343 K and normal pressure to react. The hydrogen production performance is shown in the figure. Fig. 9 As shown, the conditions for preparing the catalysts of Examples 1 to 4 and the results of the catalytic reactions are shown in Table 1.

[0075] Table 1 Performance of Ni / Cu-TiO2 nanocatalysts for catalytic hydrogen production from hydrazine hydrate prepared in Example 1 to Example 4

[0076]

[0077] As shown in Table 1, the Ni / Cu-TiO2 nanocatalysts prepared in Examples 1 to 4 all showed 100% H2 selectivity in catalyzing hydrazine hydrate to produce hydrogen. The catalytic reaction rate showed a trend of first increasing and then decreasing with the increase of the amount of copper chloride used. When the amount was 0.15 g, the Ni / Cu-TiO2 nanocatalyst prepared in Example 1 showed the best performance for the decomposition of hydrazine hydrate to produce hydrogen. It shows that the defect content of the catalyst can be regulated by regulating the amount of copper chloride used when synthesizing the Cu-TiO2 carrier. When Cu is doped into TiO2, its internal structure will be disordered, thereby generating a large number of oxygen defects. Cu-TiO2 with rich oxygen defects is not only conducive to obtaining highly dispersed small-sized metal nanoparticles, but also can adjust the electronic structure of the active metal so that its surface is in an electron-rich state. In addition, Cu-TiO2 with rich defects makes it easier for reactants to be adsorbed and activated, which may further improve the catalytic activity and make the catalytic performance of the finally prepared Ni / Cu-TiO2 nanocatalyst different in the reaction.

[0078] Example 8

[0079] The Ni / Cu-TiO2 nanocatalyst prepared in Example 1 of the present invention and the nanocatalysts prepared in Comparative Examples 1 to 3 were used to catalyze the decomposition of hydrazine hydrate to produce hydrogen. The specific process is as follows:

[0080] The catalyst was placed in a 50 mL flask containing 5 mL of deionized water, and then 12.5 mmol of NaOH was added. The amount of the catalyst was the amount of the catalyst prepared in each embodiment and comparative example. 100 uL (2 mmol) of hydrazine hydrate was added at 343 K and normal pressure to react. The hydrogen production performance diagram is shown in FIG. Fig.10 The conditions for catalyst preparation and the results of the catalytic reaction are shown in Table 2.

[0081] Table 2 Performance of each nanocatalyst prepared in Example 1 and Comparative Examples 1-3 to produce hydrogen from hydrazine hydrate

[0082]

[0083] As shown in Table 2, the Ni / Cu-TiO2 nanocatalyst prepared in Example 1 has higher activity in catalyzing hydrazine hydrate hydrogen production than the catalysts prepared in Comparative Examples 1 to 3; among them, the selectivity and activity of the Ni nanocatalyst prepared in Comparative Example 3 are relatively low, which is mainly due to the lack of support from the carrier, and the serious agglomeration of the metal nanoparticles, so the catalytic performance and hydrogen production selectivity are poor. Although the hydrogen selectivity of Ni / TiO2 prepared in Comparative Example 1 can reach 100%, the catalytic activity is much lower than that of Ni / Cu-TiO2. Although the NiCu / TiO2 nanocatalyst prepared in Comparative Example 2 has the same catalyst components and the content of Ni and Cu as the Ni / Cu-TiO2 nanocatalyst prepared in Example 1, the activity of catalyzing hydrazine hydrate decomposition to produce hydrogen is lower than that of the Ni / Cu-TiO2 nanocatalyst prepared in Example 1. The Ni / Cu-TiO2 nanocatalyst prepared in Example 1 exhibits excellent activity mainly because Cu is incorporated into the TiO2 lattice, causing some Ti-O-Ti bonds to break and reorganize and form a Cu-O-Ti interface, and the Cu-O-Ti interface can effectively improve the dispersion of Ni nanoparticles and reduce their particle size, provide a large number of active sites, and improve the electronic structure of Ni nanoparticles, thereby significantly improving the catalyst activity. In Comparative Examples 1 and 2, the Ti-O-Ti interface provided by the carrier TiO2 has poor performance in loading Ni or NiCu nanoparticles, further confirming that the Cu-O-Ti interface has a stronger interaction with Ni.

[0084] Example 9

[0085] The Ni / Cu-TiO2 nanocatalyst prepared in Example 1 of the present invention catalyzes the decomposition of hydrazine hydrate to produce hydrogen at different temperatures, and the specific process is as follows:

[0086] The catalyst was placed in a 50 mL flask containing 5 mL of deionized water, and then 12.5 mmol of NaOH was added. 100 uL (2 mmol) of hydrazine hydrate was added at 323 K, 333 K, 343 K, and 353 K under normal pressure to react. The hydrogen production performance is shown in the figure. Fig.11 The conditions for catalyst preparation and the results of the catalytic reaction are shown in Table 3.

[0087] Table 3 Catalytic hydrazine hydrate hydrogen production performance of Ni / Cu-TiO2 nanocatalyst prepared in Example 1 at different catalytic temperatures

[0088]

[0089] As shown in Table 3, the Ni / Cu-TiO2 nanocatalyst catalyzed the production of hydrogen from hydrazine hydrate with 100% H2 selectivity. The catalytic reaction rate was significantly improved with the increase of temperature. At 353 K, the prepared Ni / Cu-TiO2 nanocatalyst catalyzed the complete decomposition and dehydrogenation of hydrazine hydrate in only 2.3 min, and its conversion frequency (TOF) value was as high as 524 h -1 This is mainly attributed to the fact that high temperature can activate the catalyst and thus effectively improve the catalytic reaction activity. According to the Arrhenius equation, the activation energy of the Ni / Cu-TiO2 catalyzed hydrazine hydrate hydrogen production reaction is calculated to be 48.8 kJ / mol.

[0090] Example 10

[0091] The Ni / Cu-TiO2 nanocatalyst prepared in Example 1 of the present invention is used to catalyze the decomposition of hydrazine hydrate to produce hydrogen, and the specific process is as follows:

[0092] The catalyst was placed in a 50 mL flask containing 5 mL of deionized water, and then 12.5 mmol of NaOH was added. 100 uL of hydrazine hydrate was added at 323 K and atmospheric pressure for reaction. The reaction was repeated 20 times. The hydrogen production performance is shown in the figure below. Fig.12 shown.

[0093] from Fig.12 It can be seen that the Ni / Cu-TiO2 nanocatalyst has good cyclic stability for the decomposition of hydrazine hydrate to produce hydrogen. After repeated use 20 times, the amount of gas produced by hydrazine hydrate catalyzed by the catalyst did not decrease, and it can still maintain 73.2% of the initial catalytic activity, indicating that the catalyst has good catalytic activity and cyclic stability.

[0094] The excellent activity of the Ni / Cu-TiO2 nanocatalyst prepared by the present invention is attributed to the strong metal-support interaction, ultrafine Ni metal nanoparticles and the electronic regulation effect of the defect-rich and abundant Cu-O-Ti interface on Ni.

[0095] In summary, the method for preparing the catalyst of the present invention is simple to operate and low in cost. The obtained catalyst has the characteristics of small particle size, multiple catalytic active sites, etc., and has high catalytic activity and stability, and is a catalyst with great development prospects.

[0096] Although the description of the present invention has been quite detailed and specifically describes several described embodiments, it is not intended to be limited to any of these details or embodiments or any particular embodiment, but should be regarded as providing a broad possible interpretation of these claims in view of the prior art by reference to the appended claims, thereby effectively covering the intended scope of the present invention. In addition, the above description of the present invention is based on the embodiments foreseeable by the inventor, and its purpose is to provide a useful description, and those non-substantial changes to the present invention that have not yet been foreseen may still represent equivalent changes to the present invention.

Claims

1. A Ni / Cu-TiO2 nanocatalyst, characterized in that: The Ni / Cu-TiO2 nanocatalyst comprises Cu-TiO2 nanosheets and Ni nanoparticles dispersed on the Cu-TiO2 nanosheets; the average particle size of the Ni nanoparticles is 1.2 nm-3.0 nm, and the content of Ni is 22.6 wt%-53.9 wt%; the content of Cu in the Ni / Cu-TiO2 nanocatalyst is 2.6 wt%-5.8 wt%; The preparation method of the Ni / Cu-TiO2 nanocatalyst comprises the following steps: Disperse Cu-TiO2 powder in water, add nickel source precursor, and ultrasonicate to obtain a suspension; Adding a reducing agent to the suspension to carry out a reduction reaction until no bubbles are generated, thereby obtaining the Ni / Cu-TiO2 nanocatalyst; The mass ratio of the Cu-TiO2 powder to the nickel source precursor is 48.6-72.6:10-40; The Cu-TiO2 powder is obtained by the following steps: Titanyl sulfate, anhydrous ethanol, water, glycerol and cupric chloride are mixed and stirred to obtain a suspension; The suspension is placed in a temperature-controlled oven of an autoclave and heated to 180°C-220°C, cooled to room temperature after heating, and then washed with ethanol and water in sequence, and dried to obtain Cu-TiO2 powder; The usage ratio of the titanyl sulfate, the anhydrous ethanol, the water, the glycerol and the cupric chloride is 1.0 g-5.0 g: 10 mL-50 mL: 5 mL-10 mL: 1 mL-5 mL: 0.05 g-0.2 g; The heating time is 6 h-12 h.

2. The Ni / Cu-TiO2 nanocatalyst according to claim 1, characterized in that: The size of the Cu-TiO2 nanosheets in the Ni / Cu-TiO2 nanocatalyst is 5 nm-15 nm.

3. The Ni / Cu-TiO2 nanocatalyst according to claim 1, characterized in that: The nickel source precursor includes at least one of nickel chloride, nickel nitrate or nickel sulfate; and the reducing agent includes sodium borohydride.

4. Use of the Ni / Cu-TiO2 nanocatalyst as claimed in claim 1 in catalyzing the decomposition of hydrazine hydrate to produce hydrogen.

5. The use according to claim 4, characterized in that: The temperature at which the Ni / Cu-TiO2 nanocatalyst catalyzes the decomposition of hydrazine hydrate to produce hydrogen is 323 K-353 K.

Citation Information

Patent Citations

  • TiO2-loaded high dispersion metal catalyst and preparation method thereof

    CN103263920A

  • Preparation method and application of titanium dioxide nano tube loaded dual-metal ruthenium and nickel nano catalyst

    CN106378149A

  • Ni-doped TiO2 nanoparticle photocatalyst and preparation method thereof

    CN110787803A

  • Preparation method and applications of supported Ni / TiO2 catalyst

    CN110935452A

  • Application of copper-doped ultrathin TiO2 nanosheet loaded cobalt oxime complex in hydrogen production by photocatalytic water decomposition

    CN111151305A